Lowland-Edge Vegetation on Habitat of Proboscis Monkey (Nasalis larvatus) in Rubber Forest of Tabalong District, South Kalimantan - MOCHAMAD ARIEF SOENDJOTO; HADI SUKADI ALIKODRA; MOHAMMAD BISMARK; HERU SETIJANTO (Society for Indonesian Biodiversity, 2005)
The proboscis monkey (Nasalis larvatus) frequently visits certain lowland (baruh) and never visits other, although both lowlands are inundated during rainy season or even have no water during the dry season. Data on seedling, sapling, pole, and tree of two former lowlands and of two latter ones were collected. Important value indexes were compared based on Renkonen similarity index. Treatments on vegetation were qualitatively recorded. The former lowlands had more diverse vegetation and higher security level than the latter had. Food sources, such as Hevea brasiliensis, Syzygium stapfiana, Vitex pubescens, Elaeocarpus stipularis, and Artocarpus teysmanii were available and more abundant on the former lowlands which were poorly cared. However, such condition could change anytime, because alllowlands include in the cultivated area.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: lowland-edge vegetation, Nasalis larvatus, rubber forest, Tabalong.